Pembinaan Karakter Islami terhadap Peningkatan Akhlak Remaja di Lingkungan Masyarakat Desa Dinoyo Surabaya - Achmad IrsyadulIbad (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to improve the Islamic character and morals of adolescents through religious development activities based on active community participation. This program is implemented using an Asset-Based Community Development (ABCD) approach that emphasizes the utilization of local assets and potential, such as support from religious leaders, mosque facilities, and youth enthusiasm. The implementation method includes observation, participatory planning, implementation of development activities such as prayers, religious sermons, and worship habits, as well as joint evaluation. The results of the activities show an increase in adolescent participation in religious activities, changes in behavior towards a more positive direction, and increased spiritual and social awareness. In addition, this activity has an impact on strengthening community solidarity and creating a more religious and harmonious environment. Thus, the ABCD approach is effective in optimizing local potential to support the development of Islamic character in adolescents in a sustainable manner.